Effect of Combined Interval and Continuous Exercise Training on Gastric Emptying, Appetite, and Adaptive Responses in Men With Overweight and Obesity - Horner, Katy M.; Byrne, Nuala M.; King, Neil A. (Frontiers in Nutrition, 2021)
Background/Objectives: Characterising compensatory and adaptive responses to exercise assists in understanding changes in energy balance and health outcomes with exercise interventions. This study investigated the effects of a short-term exercise intervention (combining high intensity interval (HII) and continuous exercise) on (1) gastric emptying, appetite and energy intake; and (2) other adaptive responses including cardiorespiratory fitness, in inactive men with overweight/obesity. Methods: Fifteen men (BMI: 29.7 ± 3.3 kg/m-2) completed a 4-wk supervised exercise intervention, consisting of 5 exercise sessions per week alternating between HII (30 seconds at 100% VO2max followed by 30 seconds recovery) and continuous (at 50% VO2max) training on a cycle ergometer, progressing from 30 to 45 minutes session duration. Gastric emptying ( 13C-octanoic acid breath test), appetite (visual analogue scale), energy intake (ad libitum lunch meal), body composition (air displacement plethysmography), non-exercise activity (accelerometery) VO2max, blood pressure and fasting concentrations of glucose, insulin and ghrelin were measured before and after (≥48 h) the intervention. Results: Gastric emptying, glucose, insulin and ghrelin were unchanged, but energy intake at the ad libitum lunch test meal significantly increased at post-intervention (+171 ± 116 kcal, p<0.01). Body weight (-0.9 ± 1.1 kg), waist circumference (-2.3 ± 3.5 cm) and percent body fat (-0.9 ± 1.1%) were modestly reduced (P<0.05). VO2max increased (+4.4 ± 2.1 ml.kg.min-1) by 13% and systolic (-6.2 ± 8.4 mmHg) and diastolic (-5.8 ± 2.2 mmHg) blood pressure were significantly reduced (P≤0.01 for all). Conclusions: Four weeks of exercise training did not alter gastric emptying, indicating gastric emptying may only adapt to a higher volume/longer duration of exercise or changes in other characteristics associated with regular exercise. The combination of HII and continuous exercise training had beneficial effects on body composition, cardiorespiratory fitness and blood pressure and warrants further investigation in larger randomised controlled trials.